From Musyawarah to Islah: Constructing a Qur'anic Communication Model for Family Resilience - Sumadi Sumadi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The contemporary family institution faces unprecedented relational vulnerabilities exacerbated by macro-structural stressors. While mainstream secular family communication paradigms provide robust frameworks for functional adaptation and conflict management, they frequently marginalize the spiritual and teleological capital essential to religious populations. Addressing this epistemological gap, this conceptual study constructs the Qur'anic Communication Model for Family Resilience. Employing a rigorous thematic textual analysis, this research synthesizes classical Islamic exegesis specifically Tafsir Al-Mishbah and Tafsir Al-Munir with contemporary family communication theories. The findings propose a four-stage, linear yet recursive continuum: (1) establishing an ontological relational baseline through sakinah (tranquility) and mu’asharah bi al-ma’ruf (dignified interaction); (2) activating the deliberative protocol of musyawarah (consultation) to deconstruct autocratic power dynamics; (3) triangulating systemic crises through hakam (mediators) and islah (reconciliation); and (4) achieving eschatological transformation via ihsan (absolute benevolence) to break cycles of negative affect reciprocity. This study successfully bridges the dichotomy between classical Islamic theology and modern communication science, pivoting from deficit-based conflict resolution to an asset-based paradigm. Ultimately, this framework provides communication scholars and clinical practitioners with a culturally resonant, evidence-based toolkit for navigating severe marital dysfunction and preventing intergenerational trauma.